PENERAPAN MODEL PEMBELAJARAN DIRECT INSTRUCTION TERHADAP HASIL BELAJAR SATUAN WAKTU SISWA KELAS II SD - Ramdhani, Novia; Fauziyyah, Hana; Dewi, Nur Komala; Nabila, Nabila; Fallah, Siti Salwa Nurul; Rizwan, Muhamad; Hopeman, Teofilus Ardian (STKIP Persada Khatulistiwa Sintang, 2024)
This study aims to describe the improvement of learning outcomes of grade II elementary school students in Mathematics through the direct instruction model on the material of time units. The study adopted Classroom Action Research (CAR) with four (4) stages, namely planning, implementation, observation and reflection. The subjects of the study were 44 grade II students of Elementary School 1 Lembursawah, consisting of 24 female students and 20 male students. Data collection tools used repeat tests and observations. The data analysis technique used was the recapitulation of students' pretest and posttest scores from cycles I and II. The results of the study showed that the implementation of the direct instruction model can improve Mathematics learning outcomes of grade II students. It can be seen from the students' completeness in cycle I of 68% increasing to 84% in cycle II. It means that student learning outcomes increase gradually from cycle I to cycle II by 16%. Therefore, direct instruction model can improve students' understanding of the content of time units in the Mathematics subject of grade II elementary school.